2020
DOI: 10.1109/access.2020.2999213
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Blockchain-Fog Integration Approaches

Abstract: Fog computing (FC) is the extension of Cloud Computing (CC), from the core of the internet architecture to the edge of the network, with the aim to perform processes closer to end-users. This extension is proven to enhance security, and to reduce latency and energy consumption. Blockchain (BC), on the other hand, is the base technology behind crypto-currencies, yet is implemented in wide range of different applications. The security and reliability, along with the distributed trust management criteria proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 66 publications
0
32
0
Order By: Relevance
“…• Computationally intensive Proof of Work (PoW) need to be addressed Baniata et al [50] • Need more sophisticated security measures • Not suggested for time-critical IoT application • Lack of standardization • Problem with fast-moving clients Yao et al [42] Authentication Mechanisms…”
Section: Author Purpose Synopsismentioning
confidence: 99%
“…• Computationally intensive Proof of Work (PoW) need to be addressed Baniata et al [50] • Need more sophisticated security measures • Not suggested for time-critical IoT application • Lack of standardization • Problem with fast-moving clients Yao et al [42] Authentication Mechanisms…”
Section: Author Purpose Synopsismentioning
confidence: 99%
“…Due to the distribution of Fog nodes and its closeness to IoT devices, centralized control system like what we have in the Cloud is not possible. Therefore, new innovative techniques and solutions are required to enhance IoT users and data privacy in the Fog environment 24,123,124 such as using the blockchain technology 26,27,125‐128 . This section discusses the recommendations and future opportunities to mitigate this issue.…”
Section: Rq3—challenges and Future Directionsmentioning
confidence: 99%
“…Therefore, new innovative techniques and solutions are required to enhance IoT users and data privacy in the Fog environment 24,123,124 such as using the blockchain technology. 26,27,[125][126][127][128] This section discusses the recommendations and future opportunities to mitigate this issue.…”
Section: Iot Device Privacymentioning
confidence: 99%
“…We have previously investigated the integration of BC with FC in Baniata & Kertesz (2020) . Accordingly, we concluded that such integration may ease the optimization of several current Cloud-Edge issues, such as enhancing security, credibility, and resource efficiency.…”
Section: Introductionmentioning
confidence: 99%